The Effect of Audit Committee and Board Independence in Determining Firm Value: Evidence from Maritime Companies in Indonesia - Gani, Roydah; Masjhur, Mohamad Abdul Radjak; Ishak, Olfin; Yakup, Anggita Permata; Polapa, Lianti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Corporate governance mechanisms, particularly the roles of the audit committee and independent commissioners, are increasingly examined in relation to their influence on firm value through the quality of financial reporting. This study aims to examine the effect of the audit committee and board independence on firm value through the mediating role of financial reporting quality. The study employs a quantitative explanatory design using secondary data from annual reports of maritime transport companies during 2020–2024. Samples were selected through purposive sampling, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that the audit committee has a positive and significant effect on firm value, while board independence has no significant impact. Financial reporting quality positively affects firm value but does not mediate the relationship between the audit committee or board independence and firm value. The study contributes theoretically to corporate governance literature and provides practical insights for public companies to strengthen audit functions and the reliability of financial reporting.